In vitro larvicidal effects of ethanolic extract of Curcuma longa Linn. on Haemonchus larval stage - Nasai, Norisal; Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Marimuthu, Murugaiyah; Tijjani, Abdulnasir; Sadiq, Muhammad Abubakar; Mohammed, Konto; Lim, Eric Teik Chung; Omar, Mohamed Ariff (Veterinary World, 2016)
Aim: Gastrointestinal helminthosis is a global problem in small ruminant production. Most parasites have developed resistance to commonly available anthelminthic compounds, and there is currently an increasing need for new compounds with more efficacies. This study evaluated the in vitro effects of ethanolic extract of Curcuma longa (EECL) as a biological nematicide against third stage Haemonchus larvae (L3) isolated from sheep. Materials and Methods: Haemonchus L3 were cultured and harvested from the feces of naturally infected sheep. EECL was prepared and three concentrations; 50, 100, and 200 mg/mL were tested for their efficacies on Haemonchus L3. Levamisole at concentration 1.5 and 3 mg/mL were used as positive controls. Results: EECL showed anthelmintic activity in a dose-dependent manner with 78% worm mortality within 24 h of exposure at the highest dose rate of 200 mg/mL. There was a 100% worm mortality rate after 2 h of levamisole (3 mg/mL) admisntration. However, there was a comparable larvicidal effect between when levamisole (1.5 mg/mL) and EECL (200 mg) were administered. Conclusion: The study shows that EECL does exhibit good anthelmintic properties at 200 mg/mL which is comparable with levamisole at 1.5 mg/mL.